2019
DOI: 10.1021/acs.inorgchem.9b01125
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Detection of Hypochlorous Acid by a Bis-heteroleptic Ru(II) Complex of Pyridyl-1,2,3-triazole Ligand via C(sp2)–H Hydroxylation

Abstract: A Ru­(II) complex (Ru-1) of a substituted pyridyl-1,2,3-triazole ligand (BtPT) for highly selective “light-up” detection of hypochlorous acid is presented. An unusual anti-Markovnikov HOCl addition to the CC bond of 1,2,3-triazole and a highly specific C­(sp2)–H hydroxylation over epoxidation made Ru-1 a highly selective luminescent HOCl probe. The abnormal regio- and stereoselective HOCl addition and subsequent hydroxylation mechanism in detail is supported by the combination of ESI-MS, 1H/13C NMR spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…These results suggested the potential of Ru-azo for TGL detection of bisulfite in complicated samples containing fluorescent additives. The detection accuracy was corroborated by detecting the bisulfite concentrations in bisulfite-added (5,10, and 20 M) wine samples. As shown in Table 2, the recoveries were obtained to be 89.3-99.27% and 98.89-103.84% for phosphorescence and TGL methods, respectively, which highlighted the good precision and accuracy for detection of bisulfite in food samples.…”
Section: Background-free Tgl Detection Of Bisulfite In Food Samplesmentioning
confidence: 84%
See 1 more Smart Citation
“…These results suggested the potential of Ru-azo for TGL detection of bisulfite in complicated samples containing fluorescent additives. The detection accuracy was corroborated by detecting the bisulfite concentrations in bisulfite-added (5,10, and 20 M) wine samples. As shown in Table 2, the recoveries were obtained to be 89.3-99.27% and 98.89-103.84% for phosphorescence and TGL methods, respectively, which highlighted the good precision and accuracy for detection of bisulfite in food samples.…”
Section: Background-free Tgl Detection Of Bisulfite In Food Samplesmentioning
confidence: 84%
“…molecular and nanosized probes, has attracted enormous attention in quantitative detections of molecules and ions due to its inherent advantages, such as simplicity, speed, sensitivity and selectivity. [1][2][3][4][5][6] This requires the rational design and engineering of innovatively responsive probes to recognize and quantify the analyte in complex biological or environmental samples. [7][8][9] Despite some important advances obtained, fluorescent detection of an analyte in a complex sample remains the challenge to suppress the interference of autofluorescence from sample itself.…”
Section: Introductionmentioning
confidence: 99%
“…For the determination of HOCl, Ru(II) complex chemosensors have been developed by exploiting different response reactions, including (1) oxidation of S atom [ 188 , 189 ], (2) amines (including dibenzoylhydrazine) [ 190 , 191 ] and (3) oxime derivatives and others [ 192 , 193 ]. In 2013, Zhang et al reported a Ru(II) complex chemosensor 42 for HOCl detection and imaging [ 188 ].…”
Section: Ru(ii) Complex Chemosensors For Reactive Biomoleculesmentioning
confidence: 99%
“…To achieve this end, fluorescent probe has been demonstrated to be a very powerful tool for quantifying and real-time imaging ClOin the localization at subcellular levels and dynamics metabolism of living organisms due to its unique advantages such as high sensitivity and selectivity, simple operation, high spatial-temporal resolution for real-time detection, and imaging in biological samples [6,[10][11][12][13]. Up to now, a variety of fluorophore-derived molecular probes such as boron-dipyrromethene (BODIPY)- [14,15], coumarin- [16], benzothiazole- [17], fluorescein- [18], isolongifolanone- [19], rhodamine- [20], cyanine- [21] based organic small molecule probes and ruthenium(II)- [22], iridium(III)- [8], and lanthanide-based metal complexes have been continuously developed for detecting and imaging HOCl in organisms [23]. In addition, nanoscaled fluorescent materials have also been widely exploited to construct sensing systems for monitoring and bioimaging HOCl levels because of the intrinsic advantages of nanostructured materials such as facile preparation, friendly biocompatibility, and so on [24][25][26][27].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%